Household Waste Management as a Form of Implementation of Sustainable Development in Laikang Sub-District, Biringkanaya District, Makassar City - Jayanti Mandasari Andi Munawarah; Muhammad Rayhan Zaira; Mimi Arifin; Arifuddin .; Wiwik Wahidah Osman; Gafar Lakatupa; Sri Aliah Ekawati; Sri Wahyuni; Andi Luthfi Fadhil; Andi Siti Faatimah Mauldini Azizah; Nurul Hidayah (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2024)
Human waste becomes one of paramount issues which is faced by urban community particularly those who live in Laikang Sub-District, Biringkanaya District, Makassar City. The increasing number of population directly effected the higher waste production. Furthermore, This is exacerbated by limited capacity at landfills to accommodate waste as well as the government's lack of awareness of how important it is to manage good waste, especially household waste which has a direct impact on society. Household waste itself is dominated by organic waste, much of which comes from organic materials. Laikang Village is one of the residential areas that is active in waste management, through the PKK as women's empowerment organization. Unfortunately, organic waste management is still considered inadequate, even though it is easier than inorganic waste management in this sub-district. One solution to overcome this is to manage waste using the reduce, reuse, recycle (3R) method. Therefore, the existence of socialization on household waste management as a form of implementing sustainable development in related locations is expected to solve the problems by educating the local community. This socialization was carried out using lecture method and discussion methods with pre-test and post-test as a tool to measure participants' understanding, there are 12 of them which are part of the Laikang Sub-District PKK. The results show 100% increase in participants' understanding and knowledge regarding organic waste management. This activity provides many benefits for the sustainability of people's lives in Laikang Village.